Tropical temperature and humidity modeling for free space optical link - Al-Gailani, S. A. (Optical Society of India, 2016)
Free Space Optics (FSO) or optical wireless systems provide high data rate solution for broadband communication applications. FSO links are highly weather-dependent because different weather conditions significantly affect the link availability. In order to determine the best operational limit of an FSO link with respect to temperature and humidity, the effect of temperature and humidity on FSO network is studied in this work. Two new equations are proposed to model the effect of temperature and humidity on an FSO link operating at 850 nm in tropical climate. The first equation is developed to model the relationship between the humidity and temperature for tropical regions, while the second equation models the FSO link attenuation in terms of tropical temperature. In conclusion, it is suggested that FSO links can be operated with a normal variation of temperature and humidity in a tropical country to achieve near carrier class availability.